Вимоги ринку праці та освітні практики набуття "soft skills" здобувачами освіти другого та третього рівня підготовки спеціальності 011 – освітні, педагогічні науки - Ігнатюк, Ольга Анатоліївна (ФОП Бондаренко М. О., 2021)
У тезах обґрунтовано необхідність цілеспрямованого набуття «soft skills» майбутніми викладачами вищої школи як складової їхньої професійної спрямованості. Розглядаються освітні практики формування «soft skills» здобувачів освіти другого та третього рівня підготовки спеціальності 011 – освітні, педагогічні науки.

The theses is based the necessity of purposeful forming «soft skills» by future teachers of higher education as part of their professional orientation. The educational practices of formation of «soft skills» of students of the second and third level of training of specialty 011 – educational, pedagogical sciences are considered.
Labor market requirements and educational practices acquisition of "soft skills" by students of the second and third levels of training in speciality 011 – educational, pedagogical sciences
Keywords: педагогічна дільність; м'які навички; вища освіта; ринок праці; комунікативні навички; навички самоорганізації; креативні навички; стресостійкість; навчальний процес; pedagogical activity; soft skills; higher education; labor market; communication skills; self-organization skills; creative skills; stress resistance; educational process